Assessment of students' independency in heritage studies - Abdullah, Fadzidah; Rashid, Md. Mizanur (IIUM, 2013)
Independency in learning is crucial to ensure students‟ success in completing the course of AAR 3302: Heritage Studies. The course is considered as the capstone course of architectural educational programme in the International Islamic University Malaysia (IIUM). This research aims to assess students‟ independency in conducting their self-directing learning while doing the field work and studio work of Architectural Heritage Studies Course. This research has the objectives to examine students‟ independency in carrying out the designated tasks, and to investigate how application of knowledge and skills has been performed by students, with minimum involvement of their lecturers. The field work was carried out on building sites in Malaysia, Bangladesh, Indonesia, and Iran. Whilst the studio work, where students documents all their findings, were carried out in International Islamic University Malaysia. Quantitatively, survey was conducted by distributing questionnaire among students who enrolled in the course. Their self-assessment was sought after they had completed the course and they had clear ideas how the whole mechanisms of the course work. This research concluded that students could work independently during planning stage, field work stage, production stage, and exhibition stage of heritage study course. The research also concluded that students rate themselves as good and very good in soft skills proficiency. This research is significant in determining the quality of students‟ independency levels in managing their learning affair within multi-dimensional experience. The achievement of the course to produce independent students is essential to fulfil the urge of producing competent graduates.